Optimal placement design for picking and packing in distribution centers. (April 2021) - Rios, John; Linfati, Rodrigo; Morillo-Torres, Daniel; Derpich, Iván; Gatica, Gustavo
An efficient distribution center (DC) is one that receives, stores, picks and packs products into new logistics units and then dispatches them to points of sale at the minimal operating cost. The picking and packing processes represent the highest operating cost of a DC, and both require a suitable space for their operation. An effective coordination between these zones prevents bottlenecks and has a direct impact on the DC's operational results. In the existing literature, there are no studies that optimize the distribution of the picking and packing areas simultaneously while also reducing operating costs. This article proposes an integer nonlinear integer programming model that minimizes order preparation costs. It does so by predicting customer demand based on historical data and defining the ideal area for picking and packing activities. The model is validated through a real case study of seven clients and fifteen products. It achieves a15 % reduction in operating costs when the optimal allocation of the picking and packing areas is made.